Cronobacter Species Contamination of Powdered Infant Formula and the Implications for Neonatal Health - Kalyantanda, Gautam; Shumyak, Lyudmila; Archibald, Lennox Kenneth (Frontiers in Pediatrics, 2015)
Cronobacter is a class of Enterobacteriaceae that cause infections in neonates, especially those born prematurely. Over 90% of these infections have been linked epidemiologically to powdered infant formula (PIF). Contamination of PIF can occur at manufacture, reconstitution, or storage of reconstituted product. Intrinsic properties that enable Cronobacter to cause disease include resistance to heat, ultraviolet radiation, oxygen radicals, stomach acids, and pasteurization; an ability to utilize sialic acid (a nutrition additive to PIF that facilitates the organism’s growth and survival); and an exceptional affinity for biofilms in enteral feeding tubes. As part of ongoing endeavors to reduce the incidence of neonatal PIF-associated Cronobacter infections, the World Health Organization (WHO) and the U.S. Food and Drug Administration (FDA) have established guidelines for PIF production, preparation for infant feeding, and storage of reconstituted product.